1999
DOI: 10.1159/000016573
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Plaque pH and Glycemic Index of Various Breads

Abstract: Plaque pH was studied during 60 min in situ in 10 subjects after eating various breads. The pH response was then compared to glycemic index (GI; calculated from the incremental blood glucose area) obtained from our earlier investigations. The following four products were tested: (1) barley kernel bread (BKB), (2) BKB, sourdough–fermented (BKBS), (3) white wheat bread (WWB), and (4) syrup–sweetened wheat–rye bread (SWRB). BKB was also tested with more intensive chewing and SWRB with the addition of fat. A 5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The two different carbohydrate doses, 25 g or 50 g of glucose sugar (10% and 20% solutions) produced similar maximum decreases in plaque pH and consistent overall plaque pH excursions over 62 min. Published data have not typically controlled the carbohydrate test portion either within or between studies, with test portions varying from as low as 2 g up to 25 g of carbohydrate, limiting assessment of the cariogenic potential of different carbohydrate foods between studies [7,10,14,[16][17][18]. Furthermore, carbohydrate test portions used in previous studies may not represent realistic amounts of foods typically consumed, for example 10 mL yoghurt [27], 10 g breakfast cereal [13], or 15 mL soft drink [7], potentially restricting the real-world translation and applicability of results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two different carbohydrate doses, 25 g or 50 g of glucose sugar (10% and 20% solutions) produced similar maximum decreases in plaque pH and consistent overall plaque pH excursions over 62 min. Published data have not typically controlled the carbohydrate test portion either within or between studies, with test portions varying from as low as 2 g up to 25 g of carbohydrate, limiting assessment of the cariogenic potential of different carbohydrate foods between studies [7,10,14,[16][17][18]. Furthermore, carbohydrate test portions used in previous studies may not represent realistic amounts of foods typically consumed, for example 10 mL yoghurt [27], 10 g breakfast cereal [13], or 15 mL soft drink [7], potentially restricting the real-world translation and applicability of results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the potential impact of starchy carbohydrates on dental caries risk are more limited. In previous studies, different breads were found to produce variable decreases in plaque pH [16][17][18] and it has been hypothesized that they may contribute to higher dental caries risk. However, methodological variations amongst studies, in particular the amount of carbohydrate tested and the assessment method for plaque pH drop, restricts comparison and interpretation of results between studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the lack of the association between dmft/dmfs scores and GI/GL may be linked to the inclusion of the healthy children only because the GI may have a greater impact on patients with diabetes (Rizkalla et al , 2002). Lingström et al (2000) determined the effect of different breads on plaque pH and showed that low-GI bread resulted in less reduction in dental plaque pH than higher GI breads indicating that low-GI bread was less cariogenic. Atkinson et al (2021) investigated the effect of different starchy foods varying in their GI on acute changes in dental plaque pH and found that higher GI starchy foods produced more significant acute plaque pH decreases and larger overall postprandial glucose responses compared to lower GI starchy foods (white bread compared with canned chickpeas: −1.5 versus −0.7 pH units, p = 0.001, and 99 ± 8 mmol/L min versus 47 ± 7 mmol/L min, p = 0.026) as such higher GI foods may pose an increased the risk of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that examined the association between starchy carbohydrates and dental caries risk showed that processed starches were associated with cariogenic activity (Hancock et al, 2020). For instance, in previous studies, different types of bread caused decreases in plaque pH, indicating a contribution to higher dental caries risk (Lingström et al, 2000;Lingström et al, 1993;Mortazavi and Noin., 2011). Previous studies found evidence for a retention effect of processed starches.…”
Section: Introductionmentioning
confidence: 97%
“…Alongside the reduction of consumption of sugary foods and drinks, it is also necessary to reduce the consumption of any medicinal products containing sugar that could be prescripted or delivered over the counter to older people and replace them with other, less cariogenic ones [32,34,63]. For example, a very recent clinical study shows that a milk-based nutritional supplement with 8% sucrose used for cases of malnutrition in the elderly increases the risk of coronal and root caries [44].…”
Section: Dietmentioning
confidence: 99%